2022
DOI: 10.3390/separations9070176
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Chromatographic Strategy for the Large-Scale Extraction of Ergosterol from Tulasnellaceae sp.

Abstract: A reliable chromatographic strategy is crucial for the extraction of target compounds from natural sources as it is related to the preparation efficiency, as well as the purity of the compounds. In this study, medium-pressure normal-phase liquid chromatography and high-pressure reverse-phase liquid chromatography were combined to prepare and purify ergosterol from Tulasnellaceae sp. of Gymnadenia orchidis. First, Tulasnellaceae sp. was extracted three times (2.0 L and 2 h each time) with ethyl acetate, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…It possesses significant medicinal value, including the treatment of lung deficiency, bleeding, and cough. It also plays a crucial role in the combined treatment of type 2 diabetes (T2DM), where its tuberous root and pumpkin seeds are utilized [ 8 ]. Relevant studies have indicated a positive correlation between the compounds found in G. orchidis and its growth age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It possesses significant medicinal value, including the treatment of lung deficiency, bleeding, and cough. It also plays a crucial role in the combined treatment of type 2 diabetes (T2DM), where its tuberous root and pumpkin seeds are utilized [ 8 ]. Relevant studies have indicated a positive correlation between the compounds found in G. orchidis and its growth age.…”
Section: Introductionmentioning
confidence: 99%
“…However, research on G. orchidis has primarily focused on its pharmacological actions, with limited publications on predicting its potential suitable zones [ 10 ]. This knowledge gap is concerning given the species’ longer growth cycle and reliance on wild resources, making it increasingly rare [ 8 , 11 ]. The wild resources of G. orchidis are continuously declining, with low production but increasing demand each year [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…G. orchidis, known as "Wangla" in Tibetan medicine, possesses significant medicinal value, including the treatment of lung deficiency, bleeding, and cough (Wang et al 2022). It also plays a crucial role in the combined treatment of type 2 diabetes (T2DM), where its tuberous root and pumpkin seeds are utilized (Wang and Wang 2022). However, research on G. orchidis has primarily focused on its pharmacological actions, with limited publications on predicting its potential suitable zones (Subiah et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, research on G. orchidis has primarily focused on its pharmacological actions, with limited publications on predicting its potential suitable zones (Subiah et al 2018). This knowledge gap is concerning given the species' longer growth cycle and reliance on wild resources, making it increasingly rare (Wang and Wang 2022;Xi et al 2000). The wild resources of G. orchidis are continuously declining, with low production but increasing demand each year (Hisashi et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation